2021
DOI: 10.1159/000515566
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Recurrent Migration of the Peritoneal Dialysis Catheter into the Inguinal Hernia Sac

Abstract: We herein report the first case of a patient with recurrent migration of the peritoneal dialysis (PD) catheter into the inguinal hernia sac. A 58-year-old man suffered from end-stage renal disease due to polycystic kidney disease (PKD). A year before starting PD, a PD catheter was implanted with stepwise initiation of PD using the Moncrief-Popovich technique. He complained of drain failure and right inguinal swelling during the induction period and was diagnosed with right inguinal hernia. Further examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Home and overnight PD are cost-effective choices for renal dialysis. 15 PD is advantageous for working people, older patients, and individuals who are handicapped because of decreased hospital visits. 16 Furthermore, the recent COVID-19 outbreak, which caused the shutdown of transport and increased the demands on hospital services, highlighted the need for home dialysis, and PD was the most suitable for home dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Home and overnight PD are cost-effective choices for renal dialysis. 15 PD is advantageous for working people, older patients, and individuals who are handicapped because of decreased hospital visits. 16 Furthermore, the recent COVID-19 outbreak, which caused the shutdown of transport and increased the demands on hospital services, highlighted the need for home dialysis, and PD was the most suitable for home dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the development of serious complications can occur after initiating PD, such as intestinal obstruction or strangulation. 7,8,15 Encouraging hernia orifice examination and treatment is essential before PDC placement. In this study, all patients with ESRD who were scheduled for PDC placement were examined for hernia by the primary surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…For example, appendix entrapment was discovered as a unique cause of catheter-related obstruction in a 4-year-old boy undergoing continuous ambulatory peritoneal dialysis (CAPD), which was resolved through appendectomy and catheter replacement ( 1 ). Similarly, in 2021, a case of catheter dysfunction caused by migration into the right inguinal hernia sac was also reported ( 2 ). Another example was a 45-year-old man experiencing recurrent catheter obstruction accompanied by stomach pain, a laparoscopic examination found that the PD catheter was encircled by the sigmoid mesocolon.…”
Section: Introductionmentioning
confidence: 94%